Specific antibody synthesis in vitro. IV. The correlation of in vitro and in vivo antibody response to influenza vaccine in rhesus monkeys. - Ershler, W B (1988)
Fourteen female monkeys (Macaca mulatta) received a trivalent influenza vaccine and antibody response was determined by a change in plasma antibody content (ELISA) before and after vaccine. Lymphocyte cultures were also established from these monkeys and the level of antibody response did not correlate with mitogen-induced lymphocyte blastogenesis or natural killer cell function. In vitro anti-influenza antibody synthesis, however, was found to correlate well with the in vivo response. That is, monkeys who were non-responders, as determined by lack of change in plasma antibody content, were also non-responders in vitro. Accordingly, we believe that vaccine response is not necessarily a measure of immune competence but its measurement may, none the less, have clinical utility. The excellent correlation of in vivo and in vitro response provides predictive value for the in vitro test. Furthermore, because the correlation is good, the in vitro test may be useful as a tool in immunopharmacology and toxicology.